2021
DOI: 10.3389/fvets.2021.692389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Lactobacillus delbrueckii on Gut Microbiome and Intestinal Morphology in Weaned Piglets

Abstract: Lactobacillus delbrueckii is a Gram-positive bacterium mostly used in the dairy industry for yogurt and cheese. The present study was designed to evaluate the effects of Lactobacillus delbrueckii on serum biochemical parameters, intestinal morphology, and performance by supplementing at a dietary level of 0.1% in diets for weaned piglets. Eighty healthy weaned piglets (initial body weight: 7.56 ± 0.2 kg) were randomly divided into two feeding groups with four replicates in each group (n = 10 animals per replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Study has shown that supplementation with S. cerevisiae and Bacillus licheniformis reduced diarrhea incidence and the relative abundance of intestinal E. coli, and increased the relative abundance of Lactobacillus in ETEC-challenged piglets ( Pan et al., 2017 ). Several recent studies suggested that dietary supplementation of lactic acid bacteria (Lactobacillus johnsonii, Lactobacillus plantarum, Lactobacillus delbrueckii and Enterococcus faecalis) increased the relative abundance of Lactobacillus or Bifidobacterium spp., decreased E. coli and enhanced production of short-chain fatty acids (SCFAs) in the gut of weaning piglets ( Wang et al., 2019a ; Wang et al., 2019b ; Xin et al., 2020 ; Wang et al., 2021 ). This probiotic-mediated increase of SCFAs in the gut contributes to defend against pathogenic microbial invasion by downregulating the pH of the gastrointestinal tract, and enhances gut barrier function by providing energy to intestinal epithelial cells ( Guilloteau et al., 2010 ; D'Souza et al., 2017 ).…”
Section: Probiotics Relieve Pwd By Regulating the Intestinal Microbia...mentioning
confidence: 99%
“…Study has shown that supplementation with S. cerevisiae and Bacillus licheniformis reduced diarrhea incidence and the relative abundance of intestinal E. coli, and increased the relative abundance of Lactobacillus in ETEC-challenged piglets ( Pan et al., 2017 ). Several recent studies suggested that dietary supplementation of lactic acid bacteria (Lactobacillus johnsonii, Lactobacillus plantarum, Lactobacillus delbrueckii and Enterococcus faecalis) increased the relative abundance of Lactobacillus or Bifidobacterium spp., decreased E. coli and enhanced production of short-chain fatty acids (SCFAs) in the gut of weaning piglets ( Wang et al., 2019a ; Wang et al., 2019b ; Xin et al., 2020 ; Wang et al., 2021 ). This probiotic-mediated increase of SCFAs in the gut contributes to defend against pathogenic microbial invasion by downregulating the pH of the gastrointestinal tract, and enhances gut barrier function by providing energy to intestinal epithelial cells ( Guilloteau et al., 2010 ; D'Souza et al., 2017 ).…”
Section: Probiotics Relieve Pwd By Regulating the Intestinal Microbia...mentioning
confidence: 99%
“…1). Probiotics generally increase the concentrations of SCFAs, particularly acetate, butyrate, and propionate, in pigs [122,[171][172][173][174][175][176][177][178]. Lactate levels can also be increased by probiotic supplementation due to the abundance of lactic acid bacteria [122,173].…”
Section: Influence Of Probiotics Supplementation On Mi-crobial Metabo...mentioning
confidence: 99%
“…Probiotic supplementation in pigs preferentially enriches the phylum Firmicutes, which consists of SCFAproducing bacterial groups, such as Lactobacillaceae, Ruminococcaceae, Erysipelotrichaceae, and Lachnospiraceae [122,171,175,[178][179][180]. Furthermore, probiotic-mediated changes in the SCFA profile is associated with positive effects on the pigs, such as improved growth performance [171,172,174,175,178], improved intestinal morphology [176][177][178], stimulation of the host's immunity [171,174], protection against pathogens [181], and improvement of cognitive performance [173]. The enhancing effect of probiotics on the SCFA profile of pigs is attributed to the increased ability of the gut microbiome to metabolize carbohydrates [182,183].…”
Section: Influence Of Probiotics Supplementation On Mi-crobial Metabo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidences have confirmed that Lactobacillus and its related products can effectively regulate lipid metabolism via affecting intestinal nutrition digestion and absorption, gut microbiota and metabolites, tissue gene expression and enzyme activity ( 15 , 16 ). Lactobacillus delbrueckii as a lactobacillus strain is widely used in the dairy industry for yogurt and cheese ( 17 , 18 ). Our laboratory have identified and preserved a strain of L. delbrueckii and performed a series of researches to evaluate its role on swine production since 2009.…”
Section: Introductionmentioning
confidence: 99%